2008
DOI: 10.1038/msb.2008.20
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic gene brushes: a structure–function relationship

Abstract: We present the assembly of gene brushes by means of a photolithographic approach that allows us to control the density of end-immobilized linear double-stranded DNA polymers coding for entire genes. For 2 kbp DNAs, the mean distance varies from 300 nm, where DNAs are dilute and assume relaxed conformations, down to 30 nm, where steric repulsion at dense packing forces stretching out. We investigated the gene-to-protein relationship of firefly luciferase under the T7/E.Coli-extract expression system, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
75
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 25 publications
3
75
0
1
Order By: Relevance
“…For brush assembly we used glass slides, 18 × 18 mm 2 , with nine separate reaction chambers enclosed in a sample holder (6)(7)(8). The density of DNA brushes on the same slide and duplicate slides could be fixed to within 5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For brush assembly we used glass slides, 18 × 18 mm 2 , with nine separate reaction chambers enclosed in a sample holder (6)(7)(8). The density of DNA brushes on the same slide and duplicate slides could be fixed to within 5%.…”
Section: Methodsmentioning
confidence: 99%
“…We propose an in vitro methodology to emulate gene expression in a boundary-free compartment. The approach is based on a photolithographic biochip for fabricating dense phases of surface-bound DNA, thus forming DNA brushes (6)(7)(8). In general, brushes are formed when end-attached linear polymers collectively stretch because of excluded volume interaction when packed to distances at which there is significant overlap between neighboring molecules (9).…”
mentioning
confidence: 99%
“…[8][9][10][11] The biosynthetic reaction on surface of microchips was first realized by Buxboim et al and they developed and utilized the microchips assembled by photolithographic approach on silicon dioxide (SiO2) for controlling the cell-free expression. 7,8,12 This approach allows us to control the immobilized DNA and regulate the biosynthetic reactions in a more controlled manner. 7 Recently, it has been reported that there exists attenuation of protein synthesis in a translation coupled with a transcription system on DNA-grafted biochips, which is likely due to molecular crowding caused by the translational machinery.…”
Section: 5mentioning
confidence: 99%
“…[6][7][8] As a new research tool, cell-free gene expression has been applied to DNA-based biochips, which showed possibilities of developing synthetic biological systems and biochemical materials at nanoscale. [8][9][10][11] The biosynthetic reaction on surface of microchips was first realized by Buxboim et al and they developed and utilized the microchips assembled by photolithographic approach on silicon dioxide (SiO2) for controlling the cell-free expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation